PROFIT-SHARING BONUS PAYMENTS IN THE INCOME STATEMENT. - Mautz, R. K. (The Accounting Review, 1947)
The increased adoption of employee bonus plans by business corporations and the increased amounts paid out under such plans warrant consideration of the nature of these payments and the proper method of reporting them in the income statement. The possible variety of employee bonus plans is almost endless, and it is therefore difficult to consider them in the abstract. Hence the following assumed bonus program, patterned somewhat after an actual case, is presented as a more concrete basis for analysis. This program calls for four separate bonuses paid to four different, but in one case overlapping, employee groups as follows: (1) Factory Workers' Bonus:-a semi-annual bonus to all qualified factory workers (the qualification requirement under all four plans is six months of uninterrupted service) based upon ability and length of service. (2) General Employee Bonus:-an annual bonus to all employees including factory workers but excluding employees covered under the general staff and executive bonus plans. (3) General Staff Bonus:-an annual bonus to all executive officers and department heads except the president and the chairman of the board of directors. (4) Executive Bonus:-an annual bonus to the president and the chairman of the board of directors.